Investigating the Effects of Government Expenditure and Money Supply on Unemployment in Namibia - Shigwedha, Wilhelmine Naapopye; Kaulihowa, Teresia (Journal of Economics and Behavioral Studies, 2020)
This paper examines how government expenditure and money supply affect unemployment in Namibia. It employs the ARDL and ECM estimation techniques to establish the underlying relationship for the period 1980-2018. The results support the hypothesis that government expenditure and money supply can be used to contain unemployment. Additionally, an evidence of both long and short-run causality from government expenditure and money supply to unemployment is found. Practical policy implications indicate that in order to effectively combat unemployment problem in Namibia, the study recommends that there is a need for policy makers to ensure that the goal of employment creation is mainstreamed in all relevant fiscal and monetary policies responses in the country. Moreover, there is also a need to identify and propose policies that can help to do away with the lack of effective policy interventions